1960
DOI: 10.1113/jphysiol.1960.sp006403
|View full text |Cite
|
Sign up to set email alerts
|

The development of parotid salivary secretion in young goats

Abstract: The saliva of ruminant animals plays an important part in the control of the acidity and consistency of the contents of the reticulo-rumen sac. In the suckling ruminant, milk by-passes the reticulo-rumen by way of the oesophageal groove and flows directly into the abomasum, and the rumen remains small and contains only fluid until the animal starts to eat substantial quantities of solid food when 3-4 weeks old. A large salivary secretion is not necessary in the young animal that relies on milk for its sustenan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

1966
1966
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In calves less than a month old the parotid gland was able to produce little or no saliva. This gland has been found to be similarly immature in young goats (Kay, 1958a). The absence of parotid secretion in young calves has been noted and investigated by Krinitsin (1940) who suggested that the development of parotid secretion is related to the onset of ruminal digestion.…”
Section: Discussionmentioning
confidence: 95%
“…In calves less than a month old the parotid gland was able to produce little or no saliva. This gland has been found to be similarly immature in young goats (Kay, 1958a). The absence of parotid secretion in young calves has been noted and investigated by Krinitsin (1940) who suggested that the development of parotid secretion is related to the onset of ruminal digestion.…”
Section: Discussionmentioning
confidence: 95%
“…Clearly, not only genetic characteristics but also current diet will influence the size to which salivary glands will grow. In the young ruminant, the parotid glands only grow and mature once the animal is weaned on to solid food and develops a functional forestomach (Kay, 1960b;Wilson & Tribe, 1961). Wilson (1963) found that the parotid glands of lambs developed most rapidly in grazing animals, nearly as fast in penned lambs given milk with hay or wood shavings both parotidglands (g) in relation to body weight (kg) or metabolic body weight (kgo'75) to eat, more slowly in lambs given a purified diet which would have provided little mechanical stimulation, and scarcely at all in animals maintained on milk alone; the glands tended to regress when grazing lambs were returned to a milk diet.…”
Section: Discussionmentioning
confidence: 99%
“…The inability of the calves' parotid glands to secrete saliva as rapidly as those of adult sheep suggests that in 4-to 8-month-old calves, as in young goats (Kay, 1958a), the parotid glands have not reached full maturity.…”
mentioning
confidence: 99%